Genomic Imprinting Was Evolutionarily Conserved during Wheat Polyploidization. Issue 1 (3rd January 2018) - Yang, Guanghui; Liu, Zhenshan; Gao, Lulu; Yu, Kuohai; Feng, Man; Yao, Yingyin; Peng, Huiru; Hu, Zhaorong; Sun, Qixin; Ni, Zhongfu; Xin, Mingming
Abstract : Genes controlled by imprinting were evolutionarily conserved during wheat polyploidization. Abstract: Genomic imprinting is an epigenetic phenomenon that causes genes to be differentially expressed depending on their parent of origin. To evaluate the evolutionary conservation of genomic imprinting and the effects of ploidy on this process, we investigated parent-of-origin-specific gene expression patterns in the endosperm of diploid ( Aegilops spp), tetraploid, and hexaploid wheat ( Triticum spp) at various stages of development via high-throughput transcriptome sequencing. We identified 91, 135, and 146 maternally or paternally expressed genes (MEGs or PEGs, respectively) in diploid, tetraploid, and hexaploid wheat, respectively, 52.7% of which exhibited dynamic expression patterns at different developmental stages. Gene Ontology enrichment analysis suggested that MEGs and PEGs were involved in metabolic processes and DNA-dependent transcription, respectively. Nearly half of the imprinted genes exhibited conserved expression patterns during wheat hexaploidization. In addition, 40% of the homoeolog pairs originating from whole-genome duplication were consistently maternally or paternally biased in the different subgenomes of hexaploid wheat. Furthermore, imprinted expression was found for 41.2% and 50.0% of homolog pairs that evolved by tandem duplication after genome duplication in tetraploid and hexaploid wheat, respectively. These results suggest that genomic imprinting was evolutionarily conserved between closely related Triticum and Aegilops species and in the face of polyploid hybridization between species in these genera.